Network port connector, method of manufacturing and use thereof

CN116613591BActive Publication Date: 2026-11-03ZHEJIANG DAHUA TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310401307.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-14
Publication Date
2026-11-03
Estimated Expiration
2043-04-14

AI Technical Summary

Technical Problem

Traditional network port connectors have poor electromagnetic shielding performance and cannot effectively prevent electromagnetic radiation.

Method used

By employing composite magnetic materials, including a combination of porous graphene ellipsoids and zinc sulfide nanomaterials, and through orderly arrangement and coating with organic insulating materials, a socket for a network port connector is prepared. The thermal conductivity of graphene and the wave absorption properties of zinc sulfide are utilized to improve the electromagnetic shielding effect.

Benefits of technology

With an insertion loss of 25dB in the 20MHz-1200MHz frequency band, the absorption and shielding performance of electromagnetic waves is significantly improved, preventing electromagnetic waves from radiating outward.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116613591B_ABST
    Figure CN116613591B_ABST
Patent Text Reader

Abstract

The application relates to a network port connector and a preparation method and application thereof, and the network port connector comprises a plug and a socket, wherein the preparation raw materials of the socket comprise 20-25% of acrylonitrile, 23-28% of butadiene, 35-45% of styrene and 10-20% of composite magnetic materials in terms of mass fraction; the composite magnetic material comprises a composite material composed of porous graphene ellipsoids and zinc sulfide nanomaterials and organic insulating materials coated on the surface of the composite material; in the composite material, a plurality of the porous graphene ellipsoids are sequentially arranged to form a graphene group, and the zinc sulfide nanomaterials are fused into the graphene group. The composite magnetic material has excellent wave absorption performance, and further, the socket of the network port connector prepared from the composite magnetic material makes the network port connector have excellent electromagnetic shielding performance and can better prevent electromagnetic waves from radiating outward.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electronic industry technology, and in particular to network port connectors, their manufacturing methods and applications. Background Technology

[0002] Network transmission is present in almost all electronic devices. With the increase in transmission speed, the electromagnetic radiation problem at the connector end during network transmission is becoming increasingly serious. However, traditional network port connectors have poor electromagnetic shielding performance and cannot effectively protect against the electromagnetic radiation generated by the network port. For example, traditional RJ45 connectors are only used as communication interfaces and have virtually no electromagnetic protection effect. Summary of the Invention

[0003] Therefore, it is necessary to provide a network port connector, its manufacturing method, and its application to address the aforementioned technical problems. The network port connector has excellent electromagnetic shielding performance.

[0004] The present invention provides a network port connector, including a plug and a socket. By mass fraction, the raw materials for manufacturing the socket include: 20%-25% acrylonitrile, 23%-28% butadiene, 35%-45% styrene, and 10%-20% composite magnetic material.

[0005] The composite magnetic material includes a composite material composed of porous graphene ellipsoids and zinc sulfide nanomaterials, and an organic insulating material coated on the surface of the composite material. In the composite material, multiple porous graphene ellipsoids are arranged in an orderly manner to form a graphene group, and the zinc sulfide nanomaterials are fused into the graphene group.

[0006] In one embodiment, the porous graphene ellipsoids in the graphene group are arranged in a three-dimensional array.

[0007] In one embodiment, the porous graphene ellipsoid has an equatorial radius of 100nm-120nm and a polar radius of 200nm-250nm.

[0008] In one embodiment, the pore size of the porous graphene ellipsoid is 14nm-25nm.

[0009] In one embodiment, the ratio of the particle size of the zinc sulfide nanomaterial to the pore size of the porous carbon rod is 1:8 to 1:12.

[0010] In one embodiment, the mass ratio of the zinc sulfide nanomaterial to the graphene group in the composite magnetic material is 1:3-1:5.

[0011] The present invention also provides a method for preparing the aforementioned network port connector, comprising the following steps:

[0012] By mass fraction, 20%-25% acrylonitrile, 23%-28% butadiene, 35%-45% styrene and 10%-20% composite magnetic material are mixed and polymerized, and then dried to obtain masterbatch.

[0013] A mold is provided, and the plug is fixed in place. Then, the masterbatch is used for injection molding to obtain the mesh connector.

[0014] In one embodiment, the step of mixing and polymerizing 20%-25% acrylonitrile, 23%-28% butadiene, 35%-45% styrene and 10%-20% composite magnetic material includes: first polymerizing acrylonitrile, butadiene and styrene at a temperature of 80°C-100°C, and then mixing them with the composite magnetic material.

[0015] In one embodiment, during injection molding, the temperature of the hopper section of the injection molding machine is 140℃-150℃, the temperature of the front part of the injection molding machine barrel is 175℃-195℃, the temperature of the injection molding machine die head is 185℃-195℃, and the temperature of the mold is 190℃-210℃.

[0016] The present invention also provides an application of the aforementioned network port connector in electronic devices.

[0017] This invention, through the selection of materials and the control of the structure in composite magnetic materials, achieves an insertion loss of approximately 25 dB in the 20 MHz-1200 MHz frequency band, exhibiting excellent wave absorption performance. Furthermore, by using composite magnetic materials to fabricate network port connector sockets, the network port connectors possess excellent electromagnetic shielding performance, better preventing electromagnetic wave radiation. Attached Figure Description

[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0019] Figure 1 This is a high-magnification scanning electron microscope image of the graphene group obtained in Example 1;

[0020] Figure 2 This is a high-magnification scanning electron microscope image of the composite magnetic material prepared in Example 1;

[0021] Figure 3 Electromagnetic compatibility radiated emissions diagram for traditional RJ45 connectors;

[0022] Figure 4 Electromagnetic compatibility radiation diagram of the network port connector prepared according to the present invention. Detailed Implementation

[0023] To facilitate understanding of the present invention, it will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. Rather, these embodiments or examples are provided to make the disclosure of the present invention more thorough and complete.

[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification of this invention is for the purpose of describing particular embodiments or examples only and is not intended to limit the invention. The optional scope of the term "and / or" as used herein includes any one of two or more of the related listed items, as well as any and all combinations of the related listed items, including any two related listed items, any more related listed items, or a combination of all related listed items.

[0025] The network port connector includes a plug and a socket. The network port connector provided by the present invention, by mass fraction, comprises the following raw materials for the preparation of the socket: 20%-25% acrylonitrile, 23%-28% butadiene, 35%-45% styrene, and 10%-20% composite magnetic material.

[0026] The composite magnetic material includes a composite material composed of porous graphene ellipsoids and zinc sulfide nanomaterials, and an organic insulating material coated on the surface of the composite material. In the composite material, multiple porous graphene ellipsoids are arranged in an orderly manner to form a graphene group, and the zinc sulfide nanomaterials are fused into the graphene group.

[0027] Specifically, the zinc sulfide nanomaterials are integrated into the graphene group in the following ways: zinc sulfide nanomaterials are attached to the surface of at least a portion of the porous graphene ellipsoids, and zinc sulfide nanomaterials are filled in at least a portion of the gaps in the graphene group; furthermore, when the particle size of the zinc sulfide nanomaterials is smaller than the pore size of the porous graphene ellipsoids, the integration of the zinc sulfide nanomaterials into the graphene group also includes the presence of zinc sulfide nanomaterials within the channels of at least a portion of the porous graphene ellipsoids. Of course, the specific integration method will not have a substantial impact on the wave absorption performance.

[0028] Different structural types and materials exhibit varying electromagnetic wave conversion capabilities. In this invention, graphene and zinc sulfide are combined in terms of materials. Structurally, graphene particles are bonded together with binders such as phenolic resin to form porous graphene ellipsoids, which are then arranged in an orderly manner to form graphene clusters. Zinc sulfide nanomaterials are integrated into these graphene clusters in various ways. This allows for faster and more efficient conversion of electromagnetic waves into heat energy. Furthermore, graphene's excellent thermal conductivity enables rapid heat transfer, resulting in an insertion loss of approximately 25 dB for the composite magnetic material in the 20 MHz-1200 MHz frequency band, demonstrating excellent wave absorption performance.

[0029] Meanwhile, the composite magnetic material of this invention uses a graphene cluster composed of multiple porous graphene ellipsoids arranged in an orderly manner as the matrix, and integrates zinc sulfide nanomaterials. It exhibits a dense structure, good toughness, and is not prone to breakage failure under load. Furthermore, the composite material is coated with an organic insulating material, which not only imparts insulation to the composite magnetic material but also makes the bonding of the composite material more stable. Optionally, during the coating process, the organic insulating material can partially coat the surface of the composite material or completely coat the composite material; preferably, the organic insulating material completely coats the composite material. The organic insulating material is preferably a block polymer, such as ethylene oxide and propylene oxide block copolymer ether.

[0030] Furthermore, by using composite magnetic materials mixed with acrylonitrile, butadiene, and styrene to prepare network port connectors, the network port connectors can have excellent electromagnetic shielding performance.

[0031] To further optimize the wave absorption performance of the network port connector, composite magnetic materials can be further optimized.

[0032] For example, in composite magnetic materials, when multiple porous graphene ellipsoids are arranged in an orderly manner to form a graphene group, the porous graphene ellipsoids are arranged in a three-dimensional array; and / or, the equatorial radius of the porous graphene ellipsoids is 100nm-120nm, and the polar radius is 200nm-250nm; and / or, the pore size of the porous graphene ellipsoids is 14nm-25nm, and the ratio of the particle size of the zinc sulfide nanomaterial to the pore size of the porous graphene ellipsoids is 1:8-1:12.

[0033] Furthermore, the mass ratio of porous graphene ellipsoids to zinc sulfide nanomaterials in the composite magnetic material can be further optimized. In one embodiment, the mass ratio of zinc sulfide nanomaterials to graphene groups in the composite magnetic material is 1:3-1:5.

[0034] This invention does not limit the preparation method of composite magnetic materials; any preparation method can be used to obtain them, as long as the structure and materials meet the above-mentioned conditions of this invention, the desired effect can be achieved.

[0035] In one embodiment, the preparation method of the composite magnetic material includes the following steps: preparing graphene groups using a colloidal crystal template method, then mixing the graphene groups with zinc sulfide nanomaterials, adding organic insulating materials, heating to a viscous state, and then cooling to obtain the composite magnetic material.

[0036] The specific steps for preparing graphene groups using the colloidal crystal template method include: preparing a first formulation by mixing graphene with water, then mixing the first formulation with a binder to form a second formulation, then adding the second formulation to a colloidal crystal template and heating it under an inert atmosphere, and then cooling it under a reducing atmosphere to obtain graphene groups.

[0037] The graphene to water mass ratio is 1:2-1:4, the graphene to binder mass ratio is 10:1-10:3, the binder is preferably a resin-based binder, such as phenolic resin, the graphene to colloidal crystal mass ratio is 6:1-12:1, the colloidal crystal template is selected from polymethyl methacrylate colloidal crystal template, the heating temperature is preferably 180℃-220℃, the heating time is preferably 20h-28h, the inert atmosphere is selected from nitrogen, argon, etc., and the reducing atmosphere is selected from carbon monoxide, hydrogen, etc.

[0038] To further improve the stability of graphene, a reducing catalyst, such as SnCl2 or FeCl2, can be added to the first formulation. The mass ratio of graphene to the reducing catalyst is 1:1 to 2:1. Then, the mixture is heated in an inert gas and cooled in a reducing atmosphere to obtain a more stable first formulation. The preferred heating temperature is 220℃ to 280℃, and the preferred heating time is 4h to 8h.

[0039] It is understood that the present invention does not make any changes to the structure of the network port connector, but only improves the raw materials for the socket. Therefore, the specific structure of the network port connector can refer to the existing structure, and similarly, the manufacturing method can also refer to the existing method. For example, the socket of the present invention and the socket of the existing network port connector can both be made by injection molding and fixedly connected to the plug.

[0040] Based on this, the present invention also provides a method for preparing the aforementioned network port connector, comprising the following steps:

[0041] S1, by mass fraction, is prepared by mixing 20%-25% acrylonitrile, 23%-28% butadiene, 35%-45% styrene and 10%-20% composite magnetic material and carrying out a polymerization reaction, followed by drying to obtain masterbatch;

[0042] S2, provide a mold and fix the plug, then use the masterbatch for injection molding to obtain the mesh connector.

[0043] In step S1, the step of mixing 20%-25% acrylonitrile, 23%-28% butadiene, 35%-45% styrene and 10%-20% composite magnetic material and carrying out a polymerization reaction includes: firstly, polymerizing acrylonitrile, butadiene and styrene at a temperature of 80℃-100℃, and then mixing them with the composite magnetic material.

[0044] In step S2, during injection molding, the temperature of the hopper section of the injection molding machine is 140℃-150℃, the temperature of the front part of the barrel of the injection molding machine is 175℃-195℃, the temperature of the mold head of the injection molding machine is 185℃-195℃, and the temperature of the mold is 190℃-210℃.

[0045] Optionally, the masterbatch can be dried at a temperature of 60℃-75℃ for 2-4 hours before injection molding.

[0046] The present invention also provides an application of the aforementioned network port connector in electronic devices, which can better prevent electromagnetic waves from radiating outward.

[0047] The following specific embodiments will further illustrate the network port connector, its manufacturing method, and its application.

[0048] Example 1

[0049] Graphene powder was added to water at a mass ratio of 1:3 and mixed. Then, SnCl2 was added at a mass ratio of 1:1 to the graphene powder. The mixture was placed in an argon atmosphere and heated at 250°C for 6 hours, followed by cooling in a CO atmosphere to obtain the first formulation. The first formulation was then mixed with phenolic resin to obtain the second formulation, wherein the mass ratio of graphene powder to phenolic resin was 10:2.

[0050] The second formulation was added to polymethyl methacrylate colloidal crystals at a mass ratio of graphene to polymethyl methacrylate colloidal crystals of 8:1. The mixture was then placed in an argon atmosphere and heated at 200°C for 24 hours, followed by cooling in a carbon monoxide atmosphere to obtain the desired product. Figure 1 The graphene group shown is composed of porous graphene ellipsoids arranged in a three-dimensional array. The equatorial radius of the porous graphene ellipsoids is 100 nm, the polar radius is 210 nm, and the pore size is 18 nm.

[0051] Graphene groups and zinc sulfide nanomaterials with a particle size of 1.8 nm were added to water, with a mass ratio of graphene groups to zinc sulfide nanomaterials of 4:1. The mixture was stirred and mixed, then ethylene oxide and propylene oxide block copolymer ether were added, and the mixture was placed in an argon atmosphere and heated to 150°C until it reached a viscous state. After cooling, the desired result was obtained. Figure 2 The composite magnetic material shown.

[0052] By mass fraction, 22% acrylonitrile, 25% butadiene, 42% styrene and 11% composite magnetic material were weighed and mixed. Then, acrylonitrile, butadiene and styrene were first polymerized at 85°C, and then mixed with composite magnetic material at 150 r / s. After drying, masterbatch was obtained.

[0053] The mold is provided according to the RJ45 connector standard, and the plug is fixed. Then the masterbatch is dried at 65℃ for 3 hours. After that, the masterbatch is put into the injection molding machine. The temperature of the injection molding machine hopper is maintained at 145℃ and the stirring speed is maintained at 100r / s. The temperature of the front part of the injection molding machine barrel is 180℃ and the temperature of the injection molding machine die head is 190℃. Then the mold temperature is maintained at 200℃ for injection molding, and hydraulic equipment is used for extrusion to ensure that the raw material fills the mold. After the raw material is filled, it is cooled at room temperature to obtain the mesh connector.

[0054] Example 2

[0055] Graphene powder was added to water at a mass ratio of 1:3 and mixed. Then, SnCl2 was added at a mass ratio of 1:1 to the graphene powder. The mixture was placed in an argon atmosphere and heated at 250°C for 6 hours, followed by cooling in a CO atmosphere to obtain the first formulation. The first formulation was then mixed with phenolic resin to obtain the second formulation, wherein the mass ratio of graphene powder to phenolic resin was 10:2.

[0056] The second formulation was added to polymethyl methacrylate colloidal crystals at a mass ratio of 8:1. The mixture was then heated at 200°C for 24 hours in an argon atmosphere and cooled in a carbon monoxide environment to obtain a graphene cluster. This graphene cluster consisted of porous graphene ellipsoids arranged in a three-dimensional array, with the equatorial radius of the porous graphene ellipsoids being 100 nm, the polar radius being 210 nm, and the pore size being 18 nm.

[0057] Graphene groups and zinc sulfide nanomaterials with a particle size of 1.8 nm were added to water, with a mass ratio of graphene groups to zinc sulfide nanomaterials of 5:1. The mixture was stirred and mixed, and then ethylene oxide and propylene oxide block copolymer ether were added. The mixture was placed in an argon atmosphere and heated to 150°C until it reached a viscous state. After cooling, the composite magnetic material was obtained.

[0058] By mass fraction, 22% acrylonitrile, 25% butadiene, 42% styrene and 11% composite magnetic material were weighed and mixed. Then, acrylonitrile, butadiene and styrene were first polymerized at 85°C, and then mixed with composite magnetic material at 150 r / s. After drying, masterbatch was obtained.

[0059] The mold is provided according to the RJ45 connector standard, and the plug is fixed. Then the masterbatch is dried at 65℃ for 3 hours. After that, the masterbatch is put into the injection molding machine. The temperature of the injection molding machine hopper is maintained at 145℃ and the stirring speed is maintained at 100r / s. The temperature of the front part of the injection molding machine barrel is 180℃ and the temperature of the injection molding machine die head is 190℃. Then the mold temperature is maintained at 200℃ for injection molding, and hydraulic equipment is used for extrusion to ensure that the raw material fills the mold. After the raw material is filled, it is cooled at room temperature to obtain the mesh connector.

[0060] Example 3

[0061] Graphene powder was added to water at a mass ratio of 1:3 and mixed. Then, SnCl2 was added at a mass ratio of 1:1 to the graphene powder. The mixture was placed in an argon atmosphere and heated at 250°C for 6 hours, followed by cooling in a CO atmosphere to obtain the first formulation. The first formulation was then mixed with phenolic resin to obtain the second formulation, wherein the mass ratio of graphene powder to phenolic resin was 10:2.

[0062] The second formulation was added to polymethyl methacrylate colloidal crystals at a mass ratio of 8:1. The mixture was then heated at 200°C for 24 hours in an argon atmosphere and cooled in a carbon monoxide environment to obtain a graphene cluster. This graphene cluster consisted of porous graphene ellipsoids arranged in a three-dimensional array, with the equatorial radius of the porous graphene ellipsoids being 100 nm, the polar radius being 210 nm, and the pore size being 18 nm.

[0063] Graphene groups and zinc sulfide nanomaterials with a particle size of 1.8 nm were added to water, with a mass ratio of graphene groups to zinc sulfide nanomaterials of 3:1. The mixture was stirred and mixed, and then ethylene oxide and propylene oxide block copolymer ether were added. The mixture was placed in an argon atmosphere and heated to 150°C until it reached a viscous state. After cooling, the composite magnetic material was obtained.

[0064] By mass fraction, 22% acrylonitrile, 25% butadiene, 42% styrene and 11% composite magnetic material were weighed and mixed. Then, acrylonitrile, butadiene and styrene were first polymerized at 85°C, and then mixed with composite magnetic material at 150 r / s. After drying, masterbatch was obtained.

[0065] The mold is provided according to the RJ45 connector standard, and the plug is fixed. Then the masterbatch is dried at 65℃ for 3 hours. After that, the masterbatch is put into the injection molding machine. The temperature of the injection molding machine hopper is maintained at 145℃ and the stirring speed is maintained at 100r / s. The temperature of the front part of the injection molding machine barrel is 180℃ and the temperature of the injection molding machine die head is 190℃. Then the mold temperature is maintained at 200℃ for injection molding, and hydraulic equipment is used for extrusion to ensure that the raw material fills the mold. After the raw material is filled, it is cooled at room temperature to obtain the mesh connector.

[0066] Example 4

[0067] Graphene powder was added to water at a mass ratio of 1:3 and mixed. Then, SnCl2 was added at a mass ratio of 1:1 to the graphene powder. The mixture was placed in an argon atmosphere and heated at 250°C for 6 hours, followed by cooling in a CO atmosphere to obtain the first formulation. The first formulation was then mixed with phenolic resin to obtain the second formulation, wherein the mass ratio of graphene powder to phenolic resin was 10:2.

[0068] The second formulation was added to polymethyl methacrylate colloidal crystals at a mass ratio of 8:1. The mixture was then heated at 180°C for 24 hours in an argon atmosphere and cooled in a carbon monoxide environment to obtain a graphene cluster. This graphene cluster consisted of porous graphene ellipsoids arranged in a three-dimensional array, with the equatorial radius of the porous graphene ellipsoids being 100 nm, the polar radius being 200 nm, and the pore size being 14 nm.

[0069] Graphene groups and zinc sulfide nanomaterials with a particle size of 1.7 nm were added to water, with a mass ratio of graphene groups to zinc sulfide nanomaterials of 4:1. The mixture was stirred and mixed, and then ethylene oxide and propylene oxide block copolymer ether were added. The mixture was placed in an argon atmosphere and heated to 150°C until it reached a viscous state. After cooling, the composite magnetic material was obtained.

[0070] By mass fraction, 22% acrylonitrile, 25% butadiene, 42% styrene and 11% composite magnetic material were weighed and mixed. Then, acrylonitrile, butadiene and styrene were first polymerized at 85°C, and then mixed with composite magnetic material at 150 r / s. After drying, masterbatch was obtained.

[0071] The mold is provided according to the RJ45 connector standard, and the plug is fixed. Then the masterbatch is dried at 65℃ for 3 hours. After that, the masterbatch is put into the injection molding machine. The temperature of the injection molding machine hopper is maintained at 145℃ and the stirring speed is maintained at 100r / s. The temperature of the front part of the injection molding machine barrel is 180℃ and the temperature of the injection molding machine die head is 190℃. Then the mold temperature is maintained at 200℃ for injection molding, and hydraulic equipment is used for extrusion to ensure that the raw material fills the mold. After the raw material is filled, it is cooled at room temperature to obtain the mesh connector.

[0072] Example 5

[0073] Graphene powder was added to water at a mass ratio of 1:3 and mixed. Then, SnCl2 was added at a mass ratio of 1:1 to the graphene powder. The mixture was placed in an argon atmosphere and heated at 250°C for 6 hours, followed by cooling in a CO atmosphere to obtain the first formulation. The first formulation was then mixed with phenolic resin to obtain the second formulation, wherein the mass ratio of graphene powder to phenolic resin was 10:2.

[0074] The second formulation was added to polymethyl methacrylate colloidal crystals at a mass ratio of 8:1. The mixture was then heated at 220°C for 22 hours in an argon atmosphere and cooled in a carbon monoxide environment to obtain a graphene cluster. This graphene cluster consisted of porous graphene ellipsoids arranged in a three-dimensional array, with an equatorial radius of 110 nm, a polar radius of 210 nm, and a pore size of 17 nm.

[0075] Graphene groups and zinc sulfide nanomaterials with a particle size of 1.7 nm were added to water, with a mass ratio of graphene groups to zinc sulfide nanomaterials of 4:1. The mixture was stirred and mixed, and then ethylene oxide and propylene oxide block copolymer ether were added. The mixture was placed in an argon atmosphere and heated to 150°C until it reached a viscous state. After cooling, the composite magnetic material was obtained.

[0076] By mass fraction, 22% acrylonitrile, 25% butadiene, 42% styrene and 11% composite magnetic material were weighed and mixed. Then, acrylonitrile, butadiene and styrene were first polymerized at 85°C, and then mixed with composite magnetic material at 150 r / s. After drying, masterbatch was obtained.

[0077] The mold is provided according to the RJ45 connector standard, and the plug is fixed. Then the masterbatch is dried at 65℃ for 3 hours. After that, the masterbatch is put into the injection molding machine. The temperature of the injection molding machine hopper is maintained at 145℃ and the stirring speed is maintained at 100r / s. The temperature of the front part of the injection molding machine barrel is 180℃ and the temperature of the injection molding machine die head is 190℃. Then the mold temperature is maintained at 200℃ for injection molding, and hydraulic equipment is used for extrusion to ensure that the raw material fills the mold. After the raw material is filled, it is cooled at room temperature to obtain the mesh connector.

[0078] Example 6

[0079] Graphene powder was added to water at a mass ratio of 1:3 and mixed. Then, SnCl2 was added at a mass ratio of 1:1 to the graphene powder. The mixture was placed in an argon atmosphere and heated at 250°C for 6 hours, followed by cooling in a CO atmosphere to obtain the first formulation. The first formulation was then mixed with phenolic resin to obtain the second formulation, wherein the mass ratio of graphene powder to phenolic resin was 10:2.

[0080] The second formulation was added to polymethyl methacrylate colloidal crystals at a mass ratio of 8:1. The mixture was then heated at 220°C for 24 hours in an argon atmosphere and cooled in a carbon monoxide environment to obtain a graphene cluster. This graphene cluster consisted of porous graphene ellipsoids arranged in a three-dimensional array, with the equatorial radius of the porous graphene ellipsoids being 120 nm, the polar radius being 220 nm, and the pore size being 22 nm.

[0081] Graphene groups and zinc sulfide nanomaterials with a particle size of 2 nm were added to water, wherein the mass ratio of graphene groups to zinc sulfide nanomaterials was 4:1. The mixture was stirred and mixed, and then ethylene oxide and propylene oxide block copolymer ether were added. The mixture was placed in an argon atmosphere and heated to 150°C until it reached a viscous state. After cooling, the composite magnetic material was obtained.

[0082] By mass fraction, 22% acrylonitrile, 25% butadiene, 42% styrene and 11% composite magnetic material were weighed and mixed. Then, acrylonitrile, butadiene and styrene were first polymerized at 85°C, and then mixed with composite magnetic material at 150 r / s. After drying, masterbatch was obtained.

[0083] The mold is provided according to the RJ45 connector standard, and the plug is fixed. Then the masterbatch is dried at 65℃ for 3 hours. After that, the masterbatch is put into the injection molding machine. The temperature of the injection molding machine hopper is maintained at 145℃ and the stirring speed is maintained at 100r / s. The temperature of the front part of the injection molding machine barrel is 180℃ and the temperature of the injection molding machine die head is 190℃. Then the mold temperature is maintained at 200℃ for injection molding, and hydraulic equipment is used for extrusion to ensure that the raw material fills the mold. After the raw material is filled, it is cooled at room temperature to obtain the mesh connector.

[0084] Example 7

[0085] Graphene powder was added to water at a mass ratio of 1:3 and mixed. Then, SnCl2 was added at a mass ratio of 1:1 to the graphene powder. The mixture was placed in an argon atmosphere and heated at 250°C for 6 hours, followed by cooling in a CO atmosphere to obtain the first formulation. The first formulation was then mixed with phenolic resin to obtain the second formulation, wherein the mass ratio of graphene powder to phenolic resin was 10:2.

[0086] The second formulation was added to polymethyl methacrylate colloidal crystals at a mass ratio of 8:1. The mixture was then heated at 200°C for 24 hours in an argon atmosphere and cooled in a carbon monoxide environment to obtain a graphene cluster. This graphene cluster consisted of porous graphene ellipsoids arranged in a three-dimensional array, with the equatorial radius of the porous graphene ellipsoids being 100 nm, the polar radius being 210 nm, and the pore size being 18 nm.

[0087] Graphene groups and zinc sulfide nanomaterials with a particle size of 1.8 nm were added to water, with a mass ratio of graphene groups to zinc sulfide nanomaterials of 4:1. The mixture was stirred and mixed, and then ethylene oxide and propylene oxide block copolymer ether were added. The mixture was placed in an argon atmosphere and heated to 150°C until it reached a viscous state. After cooling, the composite magnetic material was obtained.

[0088] Weigh out 20% acrylonitrile, 28% butadiene, 37% styrene and 10% composite magnetic material by mass fraction and mix them. Then, first, polymerize acrylonitrile, butadiene and styrene at 90°C, and then mix them with composite magnetic material at 150 r / s. After drying, the masterbatch is obtained.

[0089] The mold is provided according to the RJ45 connector standard, and the plug is fixed. Then the masterbatch is dried at 65℃ for 3 hours. After that, the masterbatch is put into the injection molding machine. The temperature of the injection molding machine hopper is maintained at 145℃ and the stirring speed is maintained at 100r / s. The temperature of the front part of the injection molding machine barrel is 180℃ and the temperature of the injection molding machine die head is 190℃. Then the mold temperature is maintained at 200℃ for injection molding, and hydraulic equipment is used for extrusion to ensure that the raw material fills the mold. After the raw material is filled, it is cooled at room temperature to obtain the mesh connector.

[0090] Example 8

[0091] Graphene powder was added to water at a mass ratio of 1:3 and mixed. Then, SnCl2 was added at a mass ratio of 1:1 to the graphene powder. The mixture was placed in an argon atmosphere and heated at 250°C for 6 hours, followed by cooling in a CO atmosphere to obtain the first formulation. The first formulation was then mixed with phenolic resin to obtain the second formulation, wherein the mass ratio of graphene powder to phenolic resin was 10:2.

[0092] The second formulation was added to polymethyl methacrylate colloidal crystals at a mass ratio of 8:1. The mixture was then heated at 200°C for 24 hours in an argon atmosphere and cooled in a carbon monoxide environment to obtain a graphene cluster. This graphene cluster consisted of porous graphene ellipsoids arranged in a three-dimensional array, with the equatorial radius of the porous graphene ellipsoids being 100 nm, the polar radius being 210 nm, and the pore size being 18 nm.

[0093] Graphene groups and zinc sulfide nanomaterials with a particle size of 1.8 nm were added to water, with a mass ratio of graphene groups to zinc sulfide nanomaterials of 4:1. The mixture was stirred and mixed, and then ethylene oxide and propylene oxide block copolymer ether were added. The mixture was placed in an argon atmosphere and heated to 150°C until it reached a viscous state. After cooling, the composite magnetic material was obtained.

[0094] By mass fraction, 25% acrylonitrile, 23% butadiene, 35% styrene and 17% composite magnetic material were weighed and mixed. Then, acrylonitrile, butadiene and styrene were first polymerized at 95°C, and then mixed with composite magnetic material at 150 r / s. After drying, masterbatch was obtained.

[0095] The mold is provided according to the RJ45 connector standard, and the plug is fixed. Then the masterbatch is dried at 65℃ for 3 hours. After that, the masterbatch is put into the injection molding machine. The temperature of the injection molding machine hopper is maintained at 145℃ and the stirring speed is maintained at 100r / s. The temperature of the front part of the injection molding machine barrel is 180℃ and the temperature of the injection molding machine die head is 190℃. Then the mold temperature is maintained at 200℃ for injection molding, and hydraulic equipment is used for extrusion to ensure that the raw material fills the mold. After the raw material is filled, it is cooled at room temperature to obtain the mesh connector.

[0096] Comparative Example 1

[0097] Comparative Example 1 was carried out in accordance with Example 1, except that the second formulation was added to polymethyl methacrylate colloidal crystals and heated at 150°C for 24 hours to obtain a three-dimensional arrangement of spherical graphene groups.

[0098] Comparative Example 2

[0099] Comparative Example 2 was carried out in accordance with Example 1, except that the second formulation was added to polymethyl methacrylate colloidal crystals and heated at 190°C for 18 hours to obtain a three-dimensional arrangement of rod-shaped graphene groups.

[0100] Comparative Example 3

[0101] Comparative Example 3 was carried out in accordance with Example 1, except that carbon nanotubes were used instead of graphene to obtain a group of carbon nanotubes arranged in three dimensions of porous carbon nanotube ellipsoids.

[0102] The wave absorption performance of the network port connectors obtained in Examples 1-8 and Comparative Examples 1-3 was tested. The test methods are shown below, and the test results are shown in Table 1.

[0103] Absorption performance: Refer to GB / T32596 to test absorption bandwidth and insertion loss.

[0104] Table 1

[0105] Absorption bandwidth / GHz Insertion loss / dB Example 1 0.03-1 18-25 Example 2 0.03-1 19-25 Example 3 0.03-1 18-24 Example 4 0.04-1 17-23 Example 5 0.05-1 16-23 Example 6 0.08-1 18-23 Example 7 0.03-1 16-24 Example 8 0.03-1 18-26 Comparative Example 1 6-14 10-15 Comparative Example 2 6-14 11-17 Comparative Example 3 6-14 11-16

[0106] In addition, commercially available RJ45 connectors and the network port connector obtained in Example 1 were tested in an electromagnetic compatibility semi-anechoic chamber, and the results are as follows. Figure 3 He Ru Figure 4 As shown, from Figure 3 and Figure 4 It is known that commercially available RJ45 connectors have electromagnetic wave leakage, which can generate electromagnetic wave interference. The leakage frequencies of network ports are generally 125MHz, 250MHz, 375MHz, 500MHz, 625MHz, and 750MHz. For these frequencies where radiation exceeds the standard, the network port connector of this invention has excellent shielding effect and can better prevent electromagnetic waves from radiating outward.

[0107] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0108] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. A network port connector, comprising a plug and a socket, characterized in that, The raw materials for manufacturing the socket, by mass fraction, include: 20%-25% acrylonitrile, 23%-28% butadiene, 35%-45% styrene, and 10%-20% composite magnetic materials. The composite magnetic material comprises a composite material composed of porous graphene ellipsoids and zinc sulfide nanomaterials, and an organic insulating material coating the surface of the composite material. In the composite material, the mass ratio of zinc sulfide nanomaterials to graphene clusters is 1:3-1:

5. Multiple porous graphene ellipsoids are arranged in an orderly manner to form graphene clusters. The zinc sulfide nanomaterials are fused into the graphene clusters. The equatorial radius of the porous graphene ellipsoids is 100nm-120nm, and the polar radius is 200nm-250nm.

2. The network port connector according to claim 1, characterized in that, In the graphene group, the porous graphene ellipsoids are arranged in a three-dimensional array.

3. The network port connector according to claim 1, characterized in that, The zinc sulfide nanomaterial is integrated into the graphene group in the following manner: the zinc sulfide nanomaterial is attached to the surface of at least a portion of the porous graphene ellipsoids, and the zinc sulfide nanomaterial fills at least a portion of the gaps in the graphene group.

4. The network port connector according to claim 3, characterized in that, When the particle size of the zinc sulfide nanomaterial is smaller than the pore size of the porous graphene ellipsoid, the way in which the zinc sulfide nanomaterial is integrated into the graphene group also includes at least a portion of the pores of the porous graphene ellipsoid containing the zinc sulfide nanomaterial.

5. The network port connector according to claim 1, characterized in that, The porous graphene ellipsoid has a pore size of 14nm-25nm.

6. The network port connector according to claim 4, characterized in that, The ratio of the particle size of the zinc sulfide nanomaterial to the pore size of the porous graphene ellipsoid is 1:8 to 1:

12.

7. A method for manufacturing a network port connector as described in any one of claims 1-6, characterized in that, Includes the following steps: By mass fraction, 20%-25% acrylonitrile, 23%-28% butadiene, 35%-45% styrene and 10%-20% composite magnetic material are mixed and polymerized, and then dried to obtain masterbatch. A mold is provided, and the plug is fixed in place. Then, the masterbatch is used for injection molding to obtain the mesh connector.

8. The method for preparing the network port connector according to claim 7, characterized in that, The steps of mixing and polymerizing 20%-25% acrylonitrile, 23%-28% butadiene, 35%-45% styrene and 10%-20% composite magnetic material include: first polymerizing acrylonitrile, butadiene and styrene at a temperature of 80℃-100℃, and then mixing them with the composite magnetic material.

9. The method for preparing the network port connector according to claim 7, characterized in that, During injection molding, the temperature of the hopper section of the injection molding machine is 140℃-150℃, the temperature of the front part of the injection molding machine barrel is 175℃-195℃, the temperature of the injection molding machine die head is 185℃-195℃, and the temperature of the mold is 190℃-210℃.

10. The application of a network port connector as described in any one of claims 1-6 in an electronic device.

Citation Information

Patent Citations

  • Graphene-based infrared transmission electromagnetic shielding filter, zinc sulfide window and fabrication method of graphene-based infrared transmission electromagnetic shielding filter

    CN106653931A